Seasonal and Zone Variations in Types and Nutrient Concentrations of Feedstuffs for Dairy Cattle in Smallholder Farmers in The Eastern Province of Rwanda - Ayabagabo, Jean de Dieu; Karubiu, Migwi Perminus; Anthans, Onjoro Paul (Indian Journal of Animal Nutrition, 2020)
This study investigated the type and quality of forages used in smallholder farms dairy in three agro-ecological zones (Mayaga and peripheral Bugesera, Eastern Savanna and Central Bugesera, and Eastern plateau) of the Eastern Province of Rwanda in the four seasons of the year. Representative farms were randomly selected from the beneficiaries of Girinka programme. Daily feed types and quantities were recorded and samples were taken for proximate analysis. The analysis of variance (ANOVA) was used to assess the differences in use and quality between zones and seasons. Twenty-two (22) types of feeds were identified across the three zones and four seasons. Roadside grasses, Napier grass (Pennisetum Purpureum), and Kikuyu grass (Pennisetum clandestinum) were the only grasses that were used in the three zones throughout the year. However, Leersia grass (Leersia hexandra) and Rhodes grass (Chloris gayana) were only used during the dry season in Eastern Savanna and Central Bugesera zone. The forages harvested from roadside and weeds were the most used (56.1%) followed by the crop residues (28.7%), while the planted forages, were the second least used forages. The only legume forage identified during the study period was Calliandra (Calliandra Spp) which contributed up to 0.16% of the overall dry matter intake (DMI). The DMI was higher (p